Organisation of a community developemnt programme - Sautoy, Peter Du. (London, 1962)
The author examines recent trends in community development training, which, he suggests, are the result of a growing awareness of past inadequacies in training programmes. Even now much of the training is unsatisfactory, particularly the human relations training. In the second part of the book the author investigates the causes of these difficulties, and suggests how they may be overcome. He describes the methods used in the community development training course at the University of London Institute of Education, of which he is Senior Lecturer and Supervisor.
Keywords: Community Development